National Culture and Culinary Exploration: Japan Evidence of Heterogenous Moderating Roles of Social Facilitation - Liu, Bin; Wang, Yang; Katsumata, Sotaro; Li, Yulei; Gao, Wei; Li, Xi (Frontiers in Psychology, 2021)
This article explores the role of national culture in international tourists’ culinary consumption behavior and the moderating influence of different types of travel companions. Study 1 adopted text-mining, topical modeling approach to process useful reviews (n=7,803) posted at TripAdvisor by users from 86 countries. Study 2 develops and tests a conceptual model of the relationships between national culture and culinary choices including culinary types and range of culinary choices, based on a dataset containing 9,141 responses by tourists from over 60 countries or regions. The results reveal that both Uncertainty Avoidance and Individualism-Collectivism have significant effects on tourist food consumption categories and the range of culinary choices. The study also evaluated the role of the moderating effect of travel companions, and results supported the significant relationship on the range of culinary choices when the tourists were accompanied by different type of travel companions.